The conflict over Irish partition: From south to north to Brexit - Pinos, Jaume Castan (Politica, 2020)
This article analyses the opposition to Irish partition from its very inception to the contemporary context, dominated by Brexit-fuelled uncertainty. The article claims that while hostility to partition has experienced different methods –namely constitutional as well as violent means– and diverse degrees of intensity, there is a historical continuum of struggle against partition in Ireland. The division of Ireland into two separate polities has not just brought thousands of men and women to take up arms over the past century, it has also been the glue that has arguably fuelled the most important ideology in Ireland (both north and south); Irish republicanism. While the sovereignty debate was decisively eroded by the Good Friday Agreement, Brexit has unearthed such debate thus giving political momentum to those who decry partition. Irish Republicans, the article concludes, have gained ground to instrumentalise the political crisis generated by Brexit in order to push for their “united Ireland” aspirations.